Determinants of Hypertension among Adults in Coastal Communities: A Cross-Sectional Study at Benteng Primary Health Center - Nizam, Muhamad; Ardiansyah, Ardiansyah (Genius Journal, 2026)
Objective: Hypertension is a medical condition that can potentially increase the risk of heart disease, stroke, kidney disorders, and various other health problems. This condition often occurs without obvious symptoms, so many sufferers are unaware they have it. This study aims to determine the factors associated with the incidence of hypertension in the coastal areas of the Benteng Public Health Center in 2025. Method: This study used a quantitative approach with a cross-sectional design. The population in this study were hypertensive patients in the Benteng Public Health Center working area. The sample size was 66 individuals using purposive sampling. Data were collected using a questionnaire on the frequency of coffee consumption, seafood consumption, smoking, and sodium consumption. Data analysis was performed using the chi-square test with α < 0.05. Result: The results showed a relationship between gender and the incidence of hypertension (0.042 < 0.05). Meanwhile, coffee consumption (0.619 > 0.05), seafood consumption (0.723 > 0.05), smoking (0.240 > 0.05), and sodium consumption (0.733 > 0.05) were not associated with the incidence of hypertension. The conclusion of this study is that there is a relationship between gender and the incidence of hypertension in the Benteng Community Health Center work area. Meanwhile, coffee consumption, seafood consumption, smoking, and sodium consumption were not associated with hypertension incidence in the Benteng Community Health Center Work Area in 2025 Conclusion: This study recommends that the results can be used as literature or a reference, highlighting the need for hypertension prevention efforts that focus more on controlling related risk factors through healthy lifestyle education and routine blood pressure monitoring, supported by further research with more comprehensive methods and variables